Green Energy Powered Charging Infrastructure for Hybrid EVs - Shrivastava, Anurag; Ranga, Jarabala; Narayana, V N S L; Chiranjivi; Borole, Yogini Dilip (2021 9th International Conference on Cyber and IT Service Management (CITSM), 2021)
Nowadays, Vehicles used for transport purposes in India rely primarily on traditional sources of energy. In the various surveys, it has been observed that the automobile sector is the largest contributor of pollutants due to eminent co2 emissions resulting in the continuous degradation of the ecosystem and environment. Besides, the petroleum products usually used in automobiles are depleting promptly at a very alarming rate which is a matter of great concern. In view of that, the future lies in the more accelerated adoption of electric vehicles (EVs), which have been proved to be more energy-efficient, much higher than conventional petrol or diesel-based vehicles. This paper proposes an all-new innovative, integrated hybrid power module involving both renewable and conventional power sources fundamentally to feed the EVs. A smart integrated controller circuit has been designed for the efficient utilization of multiple energy sources and storage. Health monitoring of the whole system is taken care of to avoid disruption to the services. The scheme proposed is aimed towards reliable and affordable e-charging. Moreover, this scheme will also promote the local electricity supply's self-reliance and reduce the conventional energy flow burden. To become a critical imperative global player in the energy sector, India needs a rapid transformation by emphasizing and strengthening energy-efficient green technologies to support & nurture the ambitious goal, i.e., 'Atmanirbhar Bharat,' and to move towards a sustainable, vibrant society. The newly proposed scheme, cost optimization strategy, mathematical tools and the necessary outcome has been explained, explored, and highlighted in the subsequent sections.